Direct synthesis of dicarbonyl PCP-iron hydride complexes and catalytic dehydrogenative borylation of styrene. Issue 27 (21st June 2016) - Jiang, Shi; Quintero-Duque, Samuel; Roisnel, Thierry; Dorcet, Vincent; Grellier, Mary; Sabo-Etienne, Sylviane; Darcel, Christophe; Sortais, Jean-Baptiste
Abstract : An efficient method based on the simple metalating reagent Fe(CO)5 leads to the synthesis of cyclometalled PCP iron carbonyl pincer complexes which are active catalytic precursors for the selective dehydrogenative borylation of styrene. Abstract : A new and efficient method based on the simple metalating reagent Fe(CO)5 has been developed for the straightforward synthesis of well defined cyclometalled PCP iron carbonyl pincer complexes. The reaction proceeds cleanly under mild conditions at 30 °C and UV irradiation. Four hydride pincer complexes are synthesized and fully characterized as well as an intermediate dinuclear species. The new iron complexes are active and selective catalytic precursors for the dehydrogenative borylation of styrene with HBpin.